As much through manner as through matter: The 'Postmanist' approach to social research. Issue 1 (1st March 2014) - Rose, Ellen
Marshall McLuhan's mosaic style has been excessively scrutinized; however, the elegant prose of fellow media ecologist Neil Postman has garnered little attention. This article argues that what we find in Postman, if we look beyond the content of his work to the way in which it is presented, is an important philosophy and related approach to social research that can and should be abstracted from his treatments of advertising as parable, television as first curriculum, and technology as ideology. Intended as a counter to pseudo-scientific approaches, 'Postmanist' social research is undertaken not in order to amass data but 'to contribute to human understanding and decency' and 'improve social life'.